2016
DOI: 10.1371/journal.pone.0160939
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Activates p53 and Negatively Regulates IGF-1 Pathway in Epidermis within a Skin Cancer Model

Abstract: Exercise has been previously reported to lower cancer risk through reducing circulating IGF-1 and IGF-1-dependent signaling in a mouse skin cancer model. This study aims to investigate the underlying mechanisms by which exercise may down-regulate the IGF-1 pathway via p53 and p53-related regulators in the skin epidermis. Female SENCAR mice were pair-fed an AIN-93 diet with or without 10-week treadmill exercise at 20 m/min, 60 min/day and 5 days/week. Animals were topically treated with TPA 2 hours before sacri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 36 publications
(45 reference statements)
0
19
0
1
Order By: Relevance
“…p53 plays a vital role in the regulation if cell cycle transition, checkpoint activation, and apoptotic machinery in tumor cells, which control expression of p21 and p27 . It has been reported that TRIM59, as an E3 ubiquitin ligases, was able to interacted with p53, increasing its ubiquitination and degradation in gastric cancer cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…p53 plays a vital role in the regulation if cell cycle transition, checkpoint activation, and apoptotic machinery in tumor cells, which control expression of p21 and p27 . It has been reported that TRIM59, as an E3 ubiquitin ligases, was able to interacted with p53, increasing its ubiquitination and degradation in gastric cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that TRIM59 induced paclitaxel resistance with apoptosis inhibition. To find out the underlying mechanism, we examined several related protein and found that TRIM59 downregulated cleaved caspase 3, cleaved caspase 9, cleaved PARP, and cytochrome c release, indicating TRIM59 could reduce the activation p53 plays a vital role in the regulation if cell cycle transition, checkpoint activation, and apoptotic machinery in tumor cells, [21][22][23][24] which control expression of p21 and p27. [25][26][27] It has been reported that TRIM59, as an E3 ubiquitin ligases, was able to interacted with p53, increasing its ubiquitination and degradation in gastric cancer cells.…”
Section: Trim59 Activates Akt Signaling and Promotes P53 Ubiquitinamentioning
confidence: 99%
“…Exercise can have an impact on tumor development, growth or dissemination through several mechanisms. First, exercise might help to prevent cancer by reducing the circulating levels of several mediators, such as insulin growth factor-1 (IGF-1) [9][10][11][12][13][14], a mitogen that triggers cell proliferation [15]. Exercise can also reduce the levels of hyperphosphorylated retinoblastoma protein (Rb) in a chemically induced rat model of mammary carcinogenesis [16,17], increase ß-catenin phosphorylation in colon polyps [18,19], and reduce the levels of micro-RNA 21 [20].…”
Section: Biological Mechanisms Underpinning the Potential Anticancer mentioning
confidence: 99%
“…Exercise can upregulate tumor suppressors, such as the tumor suppressor programmed cell death protein 4 in a murine model of estrogen receptor-positive breast cancer (BC) [21]. In addition, exercise-induced catecholamines might reduce BC development through activation of the Hippo tumor suppressor pathway [22] and exercise-induced increased p53 activation, leading to tumor prevention, as shown in mouse models of skin [13,23] and lung [24] cancer.…”
Section: Biological Mechanisms Underpinning the Potential Anticancer mentioning
confidence: 99%
“…Exercise improves insulin resistance and decreases levels of insulin-like growth factor 1 in patients with breast cancer (39). Moreover, exercise is also known to enhance the expression of p21, insulin-like growth factor-binding protein-3, and PTEN, which suppress insulin-like growth factor 1 signaling in a cancer mouse model (41).…”
Section: Referencementioning
confidence: 99%